Database Integration via Mediator Approach for Integrated Applications with NFC Technology - Mohd Kamir, Yusof; Suhailan, Safei; Md Yazid, Mohd Saman; Abdullah, Embong (SEEK Digiltal Library, 2014)
Automated application using the integration of Near Field Communication (NFC) technology via mobile phone seems to be cost effective without the need to invest on expensive device reader. Some of the applications that utilized NFC technology have been explored and its data sources need to be managed. This paper proposed a suitable approach to integrate databases for application using NFC technology. Mediator approach was chosen as a bridge for application using NFC technology and data sources. Five components in mediator based: user layer, presentation layer, mediator layer, wrapper layer and database layer. Two core components in mediator approach are mediator and wrapper. S-Library is an example application using NFC technology. Three different data sources which are library database, book supplier database, student information system database as an example different data sources. The conceptual integration of these three different data sources using mediator approach is explained and the reason why mediator approach is better compared to other approaches are discussed in this paper.